Implementasi Push Notification dan Location Based Service Pada Aplikasi Smart Rekomendasi Wirausaha Untuk Pedagang Makanan Keliling - Wahyu Saputra; Eko Budi Setiawan; Angga Setiyadi (Ultimatics : Jurnal Teknik Informatika, 2019)
Food mobile traders, especially in the city of Bandung, are currently experiencing difficulties in obtaining permanent buyers and customers. 86 % traders interviewed felt that their income was increasingly decreasing due to the many buyers using online applications. The traders difficult to get buyers and it was difficult to determine the direction of his destination when trading around. Likewise, buyers who want to buy free merchandise find it difficult because they do not know the schedule of the traveling merchants and are not aware of the traders themselves. In this case, the traveling food traders and buyers need an application container that can facilitate the transaction process. Based on the results of alpha and beta tests that have been carried out at the implementation and testing stages, it can be concluded that the development of smart applications recommended by mobile food traders using push notification and location-based service based on android can make it easier for mobile traders to get buyers, and buyers are facilitated in knowing the position of the nearest traveling merchant